Eksistensi Tradisi Lisan Rejung, Guritan dan Tadut pada Masyarakat Pasemah Bengkulu - Een Syaputra; Gaya Mentari (Indonesian Journal of Social Science Education (IJSSE), 2024)
Rejung, guritan, and tadut are three types of oral traditions of the Pasemah people which in the past played an important role in social and religious life. However, due to various factors, the existence of this oral tradition is currently experiencing a decline, even threatened with extinction. This research aims to conduct an initial study of the existence of the rejung, guritan, and tadut oral traditions in the Pasemah Bengkulu community. The research was conducted using a descriptive qualitative method. Data collection was carried out using in-depth interview techniques, observation, and documentation and analyzed using the Milles & Huberman interactive model. The results of the research are: 1) the Rejung oral tradition can still be found in every region of the Pasemah community, although in number it has decreased. Currently, the Rejung tradition is no longer routinely carried out at weddings, but is often displayed at official government events and is disseminated through various social media; 2) The oral tradition of Guritan in Pasemah Bengkulu is no longer displayed when there is a death disaster because it has been replaced by religious lectures. Meanwhile, speakers are very difficult to find (only 3-5 people). Guritan poetry is very difficult to inherit/learn because it is very long and has complicated patterns; 3) the oral tradition of tadut has also not been played for a long time when there is a death disaster, namely since the increasing popularity of religious lectures or tabligh calamity events. Currently, followers can still be found in several areas such as Kedurang, Padang Guci, and Kinal, but their numbers are very small.